Donne's Devotions in the context of his early sermons : a revelation of St. John the Divine - Kearney, J (1995)
This thesis explores the relationship between Donne's Devotions Upon Emergent Occasions (1623) and his early sermons. Its underlying contention is the existence in the Devotions of a highly organized, thematic structure, which not only focusses major concerns scattered through the sermons, but places them in typological relation. Chapters 1-4 concentrate on Donne's discussion of these concerns in the sermons; Chapter 5 then demonstrates their recognizable convergence in the Devotions to trace an evolving narrative. Chapter 1 begins with beginnings, and Donne's obsessive pursuit of the origin through recreation. This is related to his fascination with the nothingness underlying birth, which he associates with God. His attempts at infinite contraction and evacuation are examined in this context, as are his images of dissolution. Chapter 2 then turns outwards to Donne's notions of public authority. But in both the political sphere and the Bible, truth is seen to vary with changing aesthetic and political needs, insofar as its ultimate reference points (Biblical translators, King) are themselves less than absolute. Chapter 3 focusses on the sermons' own attempts therefore to image the absolute, arguing that Donne positions the reader at the forefront of an increasingly refined, textual present through the telescoping of real into narrative time. The sacramental nature of the read word is suggested in this conjunction of temporal passage with liturgical present. Chapter 4 then examines the idea of division which underlies much of this discussion, as Donne deals with it explicitly and as it is manifested in the sermon structures. The paradox of the Trinity is proposed as a paradigm for Donne's ambivalence; the resolution it allows in terms of union, closure and self-containment is investigated. Chapter 5, finally, draws these threads of beginning, authority, sacramental reading and division into the tripartite framework of the Devotions, ordering and re-defining them as a series of births that mark the stages of Christian life.